(untitled) (Research, Society and Development, 2021)
Objective: to characterize the health profile, clinical outcomes of patients and the performance of the nursing team in a general adult Intensive Care Unit (ICU), in the city of Rondonópolis-MT. Methodology: mixed, cross-sectional research. Data were collected in two moments, in 2019 by internal records of the unit and the electronic medical record system of hospitalized patients and in 2020 through semi-structured interviews with ICU nursing professionals. Results: the sample consisted of 479 patient records and 21 members of the nursing team. Regarding inpatients, the majority are men, elderly, with an average age of 62.14 years and an average hospital stay of 4.6 days. The death rate in the unit was 20%, with heart disease standing out, 25.05%. In relation to the professionals of the nursing team, most of them have more than 5 years of experience in the area and they report that there is no difficulty in providing care to patients, however they have some difficulties with regard to the hospital organization. Conclusion: it is expected that the study can contribute to the knowledge of health professionals about the profile of patients admitted to the adult general ICU, making it possible to plan health care actions that are more appropriate to the patients’ needs.